Analysing Language Use In Malay Performances Of Main Puteri And Menora - Che Lah, Salasiah (Universiti Sains Malaysia, 2016)
Every society is characterised by a particular culture which is distinguished by different rituals. Language plays an important role in performing traditional rituals. In performance of rituals, language is the least researched area whereby many theories of rituals did not account for the functions of language. Language use does matter in a ritual where it is a vehicle of the intangible cultural heritage that transmits a rich oral traditions and expressions. Language is also a tool that is used by the performers and practitioners to transfer their knowledge and expertise to the community. This paper will explore the language use in Malay ritual performances of healing where the poetic interweaving speech, song and music will be analysed. A linguistic analysis will be carried out in order to understand the rich semantic and meaningful dimension of the verbal performances and narratives in the Malay performances. Two performances namely Main Puteri and Menora were chosen as these two performances place the emphasis on speech and sound. Preliminary findings reveal that the performances involve a range of poetic devices, operating a linguistic but also a non-linguistic level. With poetic language, a special vocabulary rarely used in other context is utilised. However, it is not speech alone but also the poetic of the music that is involved here. In particular, it is the musical instruments such as rebab that contributes to the performative construction of the sacredness of the event and leads to the social healing of the afflicted person. It is hoped that the findings have contributed to a better understanding of the Malay performances and rituals that demonstrate the creativity of local culture through the preservation of the local language use.